2023
DOI: 10.3390/horticulturae9010050
|View full text |Cite
|
Sign up to set email alerts
|

The Main Morphological Characteristics and Chemical Components of Fruits and the Possibilities of Their Improvement in Raspberry Breeding

Abstract: Raspberry is a delicious fruit with important nutritional and health properties for consumers. The efficiency of achieving raspberry breeding aims such as productivity, fruit quality, and adequate response to stressors, etc., depends directly on knowledge of the inheritance of traits and genetic factors of influence and their pragmatic use. In this study, the main morphological characteristics and chemical components of fruits of 24 raspberry genotypes were studied in a comparative field trial; 14 were promisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 70 publications
0
14
0
Order By: Relevance
“…Reducing sugars (glucose and fructose) were predominant sugars, while sucrose content was much lower in raspberry and blackberry fruits, 0.63-0.74% and 0.53-1.01%, respectively (Tables 1 and 2). However, in the study of Titirica et al (2023), a significantly higher sucrose content among 24 raspberry genotypes was found (1.13-1.83%).…”
Section: Chemical Parameters Of Fresh Fruit Qualitymentioning
confidence: 74%
See 1 more Smart Citation
“…Reducing sugars (glucose and fructose) were predominant sugars, while sucrose content was much lower in raspberry and blackberry fruits, 0.63-0.74% and 0.53-1.01%, respectively (Tables 1 and 2). However, in the study of Titirica et al (2023), a significantly higher sucrose content among 24 raspberry genotypes was found (1.13-1.83%).…”
Section: Chemical Parameters Of Fresh Fruit Qualitymentioning
confidence: 74%
“…One of the most important parameters of fruit maturity is the soluble solids content (SSC), which ranged from 12.72-13.34% in raspberries, regardless of the origin of the planting material and the year of harvest (Table 1). According to Titirica et al (2023), the SSC in fruits of different raspberry genotypes was 8.62-9.51%. Yang et al (2020) investigated the quality of three raspberry cultivars and indicated that the SSC depends on the degree of raspberry maturity.…”
Section: Chemical Parameters Of Fresh Fruit Qualitymentioning
confidence: 99%
“…Both broad-sense heritability (H 2 ) and narrow-sense heritability (h 2 ) were calculated, and genetic variances were partitioned based on the relationship between the half-siblings [ 118 , 119 , 120 ]. Additive, dominant, and epistatic variances were used to divide the entire genetic variance into its three components (V G = V GA + V GD + V GI ).…”
Section: Methodsmentioning
confidence: 99%
“…Recording and compiling data on important characteristics that distinguish genotypes within a species allows easy and rapid discrimination between phenotypes. It provides a better understanding of the composition and genetic diversity of the collection, allowing simple grouping of genotypes, development of core collections and generation of valuable germplasm for breeding programs [21][22].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, biochemical analyzes on fruits have become more important due to their properties for human health [22][23][24]. Although there are many biochemical studies on cultivated red raspberry fruits [14,17,18,22], biochemical analysis and study results on wild red raspberry fruits are limited in literature.…”
Section: Introductionmentioning
confidence: 99%